Fish Otoliths from the Cabarruyan Piacenzian-Gelasian fauna found in the Philippines - van Hinsbergh, Victor W.m.; Helwerda, Renate A. (Zootaxa, 2019)
We studied fish otoliths from twelve sediment samples of a well-preserved late Pliocene to early Pleistocene fauna originally from the northwest Philippines that were originally deposited in relatively deepwater marine environment. The fish fauna is systematically described, its paleoenvironmental character is explored, and its diversity is analyzed. Four unknown species have been encountered: Parascombrops schwarzhansi n. sp., Maurolicus sp., Pteropsaron sp., and Priolepis sp., of which one is described as new species and three were left in open nomenclature as their local recent counterparts are not well known yet. In addition, a variant Benthosema, Benthosema aff. fibulatum, is described. Overall, fifty-three taxa of fish otoliths were found, of which eighteen were identified at the species level and an additional twenty-seven at the genus level. Most extant species nowadays occur around the Philippines in relatively deep water (about 200 m depth), which is congruent with earlier studies on mollusks and echinoderms from the same deposits. This is the first study on a fossil fish otolith assemblage from the Philippines. Its diversity is very high and analysis by rarefaction curves suggests that additional sampling would add more fish species to the presented fauna list.